The Role of Dissonance and Schema: An Exploration of Florida Public Perception after the DWH Oil Spill - Laura M. Gorham; Joy N. Rumble; Kacie L. Pounds; Angie B. Lindsey; Tracy Irani (Journal of Applied Communications, 2016)
The agricultural and natural resources industries are no stranger to crises, particularly, large-scale crises such as the Deepwater Horizon (DWH) oil spill in 2010. Crises have an impact on how consumers view a product, and ultimately, can impact their decisions to buy or not buy products from an industry that has experienced a crisis. This qualitative study sought to evaluate consumer perceptions of Gulf seafood after the DWH oil spill, and explored the influence of schema and cognitive dissonance on consumers’ intent to consume or purchase Gulf seafood after the DWH oil spill. Focus group discussion with seafood consumers revealed participants had a pre-existing schema associated with local seafood, seafood origin, health benefits of seafood, and the safety of seafood. Dissonance was observed when participants balanced their pre-existing schemas with knowledge of the DWH oil spill as the participants discussed buying seafood, not buying seafood, and buying seafood with fear. From the findings of this study, researchers and communicators may have a better understanding of the decision-making process associated with buying a product after a crisis. Recommendations were made for agricultural communicators to develop personal messages and stories to help consumers overcome any remaining fear or dissonance associated with Gulf seafood.
Keywords: Cognitive Dissonance; Consumer Perception of Food; Deep Water Horizon Oil Spill; Schema